Paleointensity Study on the Holocene Surface Lavas on the Island of Hawaii Using the Tsunakawa–Shaw Method - Yamamoto, Yuhji; Yamaoka, Ryo (Frontiers in Earth Science, 2018)
Investigating volcanic paleointensity during the Holocene is important for linking archeointensity and sedimentary paleointensity. Across the globe, the island of Hawaii is one of the most studied subaerial locations. Many published data from Hawaii are accessible in the paleointensity databases, but it is necessary to reassess these data because they were determined with experimental protocols not incorporating a modern test for multi-domain particles and with relatively loose selection criteria. To obtain a new paleointensity dataset based on coercivity spectra rather than blocking temperature spectra, we applied the Tsunakawa–Shaw method to Holocene surface lavas collected from 34 sites on the island of Hawaii. In total, 135 successful results were obtained after applying the specimen-level selection criteria, yielding 22 site-mean Tsunakawa–Shaw paleointensities (TS dataset) that fulfilled the site-level selection criteria. We compared the TS dataset with the IZZI dataset, which includes recently reported blocking-temperature-based paleointensities determined by the IZZI Thellier method with the stringent criteria CCRIT. The cumulative distribution function (CDF) curve of the TS dataset, except for three sites, almost overlaps that of the IZZI dataset, and the medians coincide with each other, 42.9 µT (N = 19) for the TS dataset and 43.5 µT (N = 28) for the IZZI dataset. The coincidence of the CDF curves suggests equivalent reliability of the Tsunakawa–Shaw method and the IZZI Thellier method. The Holocene paleointensity variation in Hawaii is thought to be reliably characterized by both the TS dataset and the IZZI dataset: overall, the paleointensity throughout the Holocene is suggested to be higher than the present-day field. It is also inferred that there are possible decadal- and centennial-timescale large-intensity variations between ~1,800 and ~2,000 cal BP, and between ~3,000 and ~3,500 cal BP. The latter variation might be inferred as a global-scale dipolar phenomenon, as consistent paleointensity results are reported from archaeological sources in the Levant by the IZZI Thellier method.